The Role of Creatine in Enhancing Bone Health Among Postmenopausal Women - Szczepański, Michał; Dzieszko, Natalia; Borowski, Maciej; Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Kozłowska, Kinga; Książek, Tomasz Karol; Szeliga, Aleksandra; Kalinowska, Weronika; Kulasza, Paulina Sara (Quality in Sport, 2025)
Given the high popularity of creatine as a dietary supplement, its pleiotropic effects, and its well-established safety profile, it is worth considering as an adjunct therapy for osteoporosis—a condition that predominantly affects postmenopausal women due to hormonal changes, particularly a decline in estrogen levels—and has become a silent epidemic of the 21st century. Creatine may indirectly enhance muscle mass and strength, leading to increased mechanical stress on bones, and some studies suggest that creatine might also directly influence osteoblast activity and bone metabolism, potentially promoting bone formation. These direct and indirect mechanisms may improve bone health in at-risk women, reducing the risk of falls and fractures and ultimately contributing to a better quality of life. This research explores the effects of creatine on bone remodeling, metabolic activity, resistance training performance, and its potential anti-inflammatory properties in the context of skeletal health maintenance. It also examines appropriate creatine dosing in older adults—which typically does not require a loading phase—and evaluates the safety of creatine use in aging women.